The Relationship Of Gadget Addiction And Diet Pattern To The Body Mass Index (BMI) Of Adolescents Ages 15-17 Years Old - Baiq Meisy Arum Anjani; Danang Nur Adiwibawa; Irsandi Rizki Farmananda; Kadek Dwi Pramana (Jurnal Psikiatri Surabaya, 2023)
Introductions: The development of technology and information is running very fast, marked by progress in information and technology, one of which is gadgets. This affects excessive use of gadgets, and low physical activity makes eating patterns inappropriate, which can affect nutritional status in the long run. Objectives: To analyze the relationship between gadget addiction and eating habits on the body mass index of adolescents aged 15-17. Methods: Observational analytic, quantitative research with cross-sectional study design. The sampling technique used random simple sampling. The Chi-Square correlation test analyzed the data obtained. Results: The prevalence value of heavy gadget addiction in respondents was 89 people (27.6%). The prevalence value of frequent eating patterns in respondents was 146 people (45.2%). The prevalence value of the overweight body mass index in respondents was 43 people (13.3%). There was a significant relationship between addiction to playing gadgets (smartphones) and body mass index. P-value 0.004 (p-value < 0.05). There is an essential relationship between diet and body mass index. P-value p-value 0.038 (p-value < 0.05). Conclusions: There is a relationship between addiction to gadgets (smartphones) and eating patterns on the body mass index of adolescents.